The variables don´t are pizzas. The miracle is the multiplication of bread don’t multiplication of sub-hypotheses - Díaz Flores, Francis (2021)
This article explains why it is irrelevant to formulate sub-hypotheses, when in an explanatory research or non-causal correlation research, two variables are worked on, with the aim that thevast majority of graduate students of the universities of Peru are doing so, as a general practice, in their thesis, and whose origin is unknown. These researchers divide the independent variables into their dimensions and, from each of them, formulate the sub-hypotheses. Some researchers formulate sub hypotheses by decomposing the independent variable and dependent variable into their respective dimensions. Others break down the dependent variable into its dimensions to formulate sub-hypotheses. Sub-hypotheses are often raised when in multivariate or factorial  investigations, more than one independent variable is worked on, it is possible to formulate sub-hypotheses from each of the independent variables. In this case, the formulation of sub-hypotheses is done when the hypothesis test strategy is the Variance Analysis.